E-Government Implementation in the Village General Administrative Electronic System (SEDULUR) Program - Hery Nariyah; Nursahidin Nursahidin; Darwanto Darwanto; Agus Purwanto; Ade Setiadi; Moh Sutarjo (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: E-government is one of the government's efforts to develop the implementation of electronic-based government activities in order to improve the quality of service to various parties effectively and efficiently. In the context of implementing e-government in Cirebon City, Cirebon City is carrying out a smart city or smart city movement with its vision of realizing Cirebon as a creative, innovative, synergistic and competitive smart city in 2028. Lots of programs have been implemented as supporters of the realization of the smart city movement in the city of Cirebon. Research with the title